2009
DOI: 10.1111/j.1567-1364.2009.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering ofSaccharomyces cerevisiae for production of carboxylic acids: current status and challenges

Abstract: To meet the demands of future generations for chemicals and energy and to reduce the environmental footprint of the chemical industry, alternatives for petrochemistry are required. Microbial conversion of renewable feedstocks has a huge potential for cleaner, sustainable industrial production of fuels and chemicals. Microbial production of organic acids is a promising approach for production of chemical building blocks that can replace their petrochemically derived equivalents. Although Saccharomyces cerevisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
115
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 121 publications
1
115
0
2
Order By: Relevance
“…Equilibrium ratios were calculated on the assumption that all three compounds are exported via monoanion proton symport, on a proton motive force across the yeast plasma membrane of Ϫ150 mV and an intracellular pH of 7 and on the following acid dissociation (pK a ) constants: malate, 3.46 and 5.10; pyruvate, 2.39; succinate, 4.16 and 5.61. Calculations were performed as described earlier (1,43 Not only does the culture pH impact the thermodynamics of product export, but also it has been reported that a low extracellular pH, combined with the presence of organic acids, can decrease the cytosolic pH (11,28). With a pK a of 6.35, the equilibrium between carbon dioxide and bicarbonate would be strongly influenced by changes in the intracellular pH.…”
Section: Discussionmentioning
confidence: 99%
“…Equilibrium ratios were calculated on the assumption that all three compounds are exported via monoanion proton symport, on a proton motive force across the yeast plasma membrane of Ϫ150 mV and an intracellular pH of 7 and on the following acid dissociation (pK a ) constants: malate, 3.46 and 5.10; pyruvate, 2.39; succinate, 4.16 and 5.61. Calculations were performed as described earlier (1,43 Not only does the culture pH impact the thermodynamics of product export, but also it has been reported that a low extracellular pH, combined with the presence of organic acids, can decrease the cytosolic pH (11,28). With a pK a of 6.35, the equilibrium between carbon dioxide and bicarbonate would be strongly influenced by changes in the intracellular pH.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli and yeasts have proven to be excellent biocatalysts for metabolic engineering (11,12). However, both are inhibited by furan aldehydes (7,8,(13)(14)(15) and both contain NADPH-dependent oxidoreductases that convert furfural and hydroxymethylfurfural (dehydration product of hexose sugars) into less toxic alcohols (15)(16)(17).…”
mentioning
confidence: 99%
“…Additional advantages of this organism are that its genome has been fully sequenced and that it is considered by the American Food and Drug Administration (FDA) as an organism generally regarded as safe (GRAS) (6). In addition, in several recent studies, the yeast S. cerevisiae has been proposed as a cell factory for the production of bulk chemicals, such as malic, lactic, and citric acid from renewable substrates (1,30,36,42,43).…”
mentioning
confidence: 99%